Decree No. 569 of the year 2008 Amending Certain Provisions Of the Executive Regulation Of Law No.161/1998 Concerning the Protection of National Economy Against the Effects Resulting From The Malignant Practices Of International Trade = قرار إداري رقم 569 لسنة 2008 بتعديل بعض أحكام اللائحة التنفيذية للقانون رقم 161 لسنة 1998 بشأن حماية الاقتصاد القومي من الآثار الناجمة عن الممارسات الضارة في التجارة الدولية / Prime Minister - Egypt. Prime Minister (2025)
The ministry of trade and industry decree no. 569 of the year 2008 amending certain provisions of the executive regulations of law no. 161 of the year 1998 concerning the protection of national economy against the effects resulting from the malignant practices of international trade وزارة التجارة والصناعة قرار رقم 569 لسنة 2008 بتعديل بعض أحكام اللائحة التنفيذية للقانون رقم 161 لسنة 1998 بشأن حماية الاقتصاد القومى من الآثار الناجمة عن الممارسات الضارة فى التجارة الدولية